DEVELOPING ISLAMIC MATERIAL BASED ON SPIRIT OF NATIONAL TOLERANCE - CHOIRUL MAHFUD (JURNAL PENDIDIKAN GLASSER, 2019)
In recent years, discussion of national tolerance continues to emerge. Not a few who discussed it in the scientific perspective or religion as a source of teachings and actions. In studying Islam, it is generally necessary to depart from two approaches, namely historical and normative. Choosing one between them is a reckless way. Similarly, in reading the dynamics of Islam in the contemporary era like today. Here, the developing Islamic material based on the spirit of national tolerance is very important to improve positive horizon in the country.